Madlen i sobaka - Bemelmans, Ludwig, 1898-1962 (Rozovyĭ zhiraf, 2011)
A hound rescues a schoolgirl from the Seine, becomes a beloved school pet, is chased away by the trustees, and returns with a surprise.